Discussion on the Role of Business Administration in Promoting Economic Development - Wang, Shuo (International Journal of Global Economics and Management, 2024)
This article delves into the pivotal role of business administration in driving economic development. It elucidates the core functions of business administration and its synergy with economic progress. Specific areas where business administration catalyzes development, such as innovation, marketing, resource allocation, and strategy, are explored. Additionally, it examines the challenges encountered by business administration in advancing economic growth, including legal frameworks, cultural shifts, technological evolution, and global competition. By elucidating these dynamics, the article aims to underscore the indispensable contribution of business administration to fostering sustainable economic development.